Financial Inclusion Profile: Determinant and Barriers - Kaligis, Novi V.B.; Tewal, Bernhard; Maramis, Joubert B.; Mangantar, Maryam (International Journal of Economics and Financial Issues, 2018)
The policies arranged by the government of the Republic of Indonesia in the efforts to develop rural areas and border areas, such as North Sulawesi (which is in the border of Indonesia-Philippines), is interesting to observe, particularly on the aspect of financial inclusion in Small and Medium Enterprise (SME). The research aims at examining the determinant and obstacles of financial inclusion in North Sulawesi. The results show that Age and Gender do not significantly influence financial inclusion, especially with the dependent variable of formal account. Meanwhile, other variables, the status of formal account and the Automatic Teller Machine (ATM) cards, do not have significantly influence. Similarly, education has also dependent variables. The difference is the determinant of the dependent variables. The number of formal account and the ATM significantly influence the financial inclusion, but not the model of the status of the formal account. For the obstacles, there are six factors influencing the financial inclusion. Those are lack of business management, bad experience with the bank, less supporting business condition, religion and family, and various documents of credit requirements. Keywords: Financial Inclusion, Determinant, Obstacles, SME JEL Classifications: E44, G2, G32